Beyond optimal performance: Mental toughness profiles and indicators of developmental success in adolescent cricketers - Gucciardi, Daniel; Jones, M. (Human Kinetics, 2012)
The purposes of the current study were to identify mental toughness profiles in adolescent cricketers and examine differences between these profiles on developmental assets and negative emotional states. A sample of 226 community cricketers (125 New Zealanders and 101 Australians; male n = 210) aged between 10 and 18 years (Mage = 14.41 years; SD = 2.11) completed a multisection, online survey containing measures of mental toughness, developmental assets, and negative emotional states.The results of hierarchical (Ward’s method) and nonhierarchical (k means) cluster analyses revealed three mental toughness profiles characterized by low, moderate, and high levels of all five mental toughness assets (i.e., affective intelligence, desire to achieve, self-belief, attentional control, resilience). Those cricketers with high levels of mental toughness reported possession of more developmental assets and lower levels of negative emotional states when compared with cricketers with the moderate levels of mental toughness. No statistically significant differences existed between the moderate and low levels of mental toughness profiles. These findings provided preliminary evidence to suggest that mental toughness might be viewed not only from the traditional view of optimal performance but also from a stance that may represent a contextually salient representation of thriving in youth sport settings.